The Dilemma Of Financial Accountability Of Student Organizations: A Case Study At The Faculty Of Economics And Business, Brawijaya University - Siti Nurcholifah; Gugus Irianto; Ali Djamhuri (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
Universities generally have student organizations in the form of Student Activity Units (SAU). The faculty’s budget allocation is used to finance SAU. In addition, SAU management submits to the faculty a Financial Accountability Report (FAR). The faculty expects SAU to use 100% of the budget, ensuring that there will be no budget cuts in the future. It encourages SAU to explore numerous options in order to fully use the funding. The purpose of this study is to determine what, why, and how the financial accountability dilemma of SAU happens at the Faculty of Economics and Business, Brawijaya University. This qualitative research was performed at the Faculty of Economics and Business, Brawijaya University. The interview method was utilized to collect data using a case study approach. In this study, there were five informants: three informants from SAU and 2 others from the faculty. The findings revealed that SAU had a dilemma between presenting an accountable FAR but facing a budget cut the next period or being opportunistic by attempting to make the budget appear to be fully used so that there were no budget cutbacks in the following period. SAU was forced to put in more effort to fully use the budget's realization, notably through FAR manipulation.